Law and Political Economy - Gaudreau, Claude (Relations industrielles / Industrial Relations, 1952)
This article is a summary of the respective opinions of Gaëtan Pirou, economist and of Georges Ripert, jurist, on Law and Political Economy, and the author's personal position on the subject. Is Political Economy a human discipline, a science, a doctrine? Does there not exist between the two, relationships and contacts that would be useful and perhaps even necessary to the two kinds of specialists to understand? The author points out certain interesting distinctions to be noted between economic fact and juridical fact, scientific law and positive law, moral science and experimental science. He concludes in emphasizing that the law, economics and other social disciplines complete one another to advantage with all the consequences arising from this.